Skateboarding Women: Building Collective Identity in Cyberspace. (December 2014) - MacKay, Steph; Dallaire, Christine
This article reconsiders the Skirtboarders' blog, produced by a crew of female skateboarders, as a space where crew members attempt to reflexively start a movement and, in doing so, construct and circulate a wider collective identity (Taylor & Whittier, 1992). Through a discourse analysis of blog comments and user interviews, we attempt to understand how young women who visit the blog interpret (re)presentations of female skateboarders and whether they become engaged in the movement to promote skateboarding among women. Do they adopt this collective subjectivity? While the analysis suggests that they do feel part of the movement, it raises the issue of blog user access to the more specific "Skirtboarder" identity.